2006
DOI: 10.2105/ajph.2004.053942
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Population-Based Study Identifying Health Disparities Between American Indians/Alaska Natives and the General Populations Living in Select Urban Counties

Abstract: We found health disparities between American Indians/Alaska Natives and the general populations living in selected urban areas and nationwide. Such disparities can be addressed through improvements in health care access, high-quality data collection, and policy initiatives designed to provide sufficient resources and a more unified vision of the health of urban American Indians/Alaska Natives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(129 citation statements)
references
References 15 publications
3
122
1
Order By: Relevance
“…There is also are an increasing percentage of American Indians moving to urban centres, which presents a considerable barrier for obtaining health care from IHS clinics (46). According to the 2000 U.S. Census, approximately 61% of American Indians and Alaska Natives report living in an urban area (47).…”
Section: Barriers To Health Carementioning
confidence: 99%
See 1 more Smart Citation
“…There is also are an increasing percentage of American Indians moving to urban centres, which presents a considerable barrier for obtaining health care from IHS clinics (46). According to the 2000 U.S. Census, approximately 61% of American Indians and Alaska Natives report living in an urban area (47).…”
Section: Barriers To Health Carementioning
confidence: 99%
“…However, there are only approximately 34 IHS-funded urban Indian health organizations that serve over 400,000 urban-dwelling American Indians and Alaska Natives. Although IHS does not routinely report data on urban American Indians or Alaska Natives, studies suggest that the level of health disparities are similar to those residing on rural reserves (48) and considerably worse than the general urban population (46). For example, a study that examined the travel to rural reserves among a group of low-income urban American Indian respondents found that more travel to rural reserves was associated with greater presence of lung disease, absence of thyroid and mental problems and greater dissatisfaction with health care (48).…”
Section: Barriers To Health Carementioning
confidence: 99%
“…18 A nationwide population-based study found that mortality rates from CLD/cirrhosis were twice as high among urban AI/AN than for the general population. 51 The agespecific CLD death rate in AI/AN was over twice as high as in US whites and blacks, and over 3 times as high as in Asian/Pacific Islanders. 18 Although rates observed in other racial groups decreased, the ageadjusted death rates from CLD increased among AI/ AN from 1990 to 1998.…”
Section: Discussionmentioning
confidence: 91%
“…Two studies from the past decade reported the overall, age-adjusted death rates due to CLD in AI/AN populations was 25.5-28.7 per 100 000 compared to 10.4-11.6 per 100 000 in the general population [4,5] . Moreover, CLD disproportionately strikes young adults; it was the second-leading cause of death among AI/ANs 25-44 years old [1] .…”
Section: Epidemiology Of Cldmentioning
confidence: 99%